Produksi Komponen Darah Packed-Red Cell (PRC), Liquid Plasma (LP), Thombocytes Concentrates (TC) dan Fresh-Frozen-Plasma (FFP) di UDD PMI Kabupaten Bojonegoro - Muflikhah, Nina Difla; Nuraini, Fatia Rizki; Anggita, Etri Sukma (poltekkes kemenkes pontianak, 2023)
The processing of blood components is an act of separating the components of donor blood through a process by taking into account the quality and safety of blood component products. Its process produce various type of blood component, such as Packed Red Cell, Liquid Plasma, Thrombocytes Concentrate and Fresh Frozen Plasma. The quantity of each blood production depends on the mount of demant from hospital to threat the patient for transfusion. Indonesia Red Cross especially in Blood Donor Unit of each region have a important duty to collect and process the whole blood component as much as it needed. This type of research is a descriptive study with a cross sectional approach. The population used was the production of PRC, LP, TC and FFP Â at UDD PMI Bojonegoro from June to July 2022 as many as 2124 kolf. The sampling technique used purposive sampling. Data analysis using univariate analysis which is presented in the form of a frequency distribution table and ghraphic for daily production. Production of blood components as much as 2124 kolf, Production of PRC as 984 kolf (46%), LP as 904 kolf (43%0, TC as 200 kolf (9%), and FFP as 36 kolf (2%). The highest blood component production is PRC, followed by LP, TC and FFP, respectfully. Â